Analysis of Abuse of Dominant Position through Secret Agreements by PT. Forisa Nusapersada - Winanda, Lutgardis Dianika; Irwan, Raden; Basuki, Rahmad; Warsono, Warsono; Pangaribuan, Zekson (Jurnal Indonesia Sosial Sains, 2025)
The regulation in Law Number 5 Year 1999 on the Prohibition of Monopolistic Practices and Unfair Business Competition broadly addresses prohibited agreements, activities, and dominant positions. This study uses a normative juridical research method with the aim of analyzing the closed agreements made by PT Forisa Nusapersada based on Law No. 5 of 1999, Commission Regulation No. 3 of 2009, and Commission Regulation No. 6 of 2010. The research specifically focuses on the abuse of the dominant position through the "Pop Ice The Real Ice Blender" program, which is alleged to have limited market competition and harmed consumer choice. The findings indicate that PT Forisa Nusapersada’s actions constitute an abuse of its dominant position, as it used its market share of 90.09% to 92.16% to monopolize the market by limiting competitors' ability to sell similar products and forcing retailers to display Pop Ice products exclusively. This violation is supported by the findings in KPPU Decision Number 14/KPPU-L/2015, which continued until the Supreme Court Decision Number: 1106 K/Pdt.Sus-KPPU/2017. The research concludes that such strategies violate the provisions of Article 25 paragraph (1) of Law No. 5 of 1999 by unfairly restricting market access and consumer choice, thus undermining fair competition.